Optimasi Pemilihan Soal Ujian Try Out Menggunakan Algoritma Greedy Berdasarkan Tingkat Kesulitan dan Waktu Pengerjaan - Zelly Apriza; Septi Mujiranda; Tata Sutabri (Jurnal Manajemen Informatika & Teknologi, 2025)
The selection of appropriate questions for the trial exam is one of the main factors in objectively evaluating the readiness of participants. This process not only considers the level of difficulty of the questions, but also the duration of the work required. This study proposes the application of the greedy algorithm as a method for selecting questions based on these two main parameters. The greedy algorithm was chosen because it can provide a quick solution by selecting the best option at each step of decision making. In practice, the system will sort the questions based on the ratio of the value between the level of difficulty and the time required to complete them, then select questions until the maximum time is reached. The test results show that this method can form a collection of questions that are balanced between the time to complete and the level of difficulty. This method can also be applied in various trial exam situations with a set time. This study offers an initial overview of the use of the greedy algorithm in developing an efficient and responsive question selection system.